Optimalisasi Microsoft Excel dalam Penyusunan Laporan Keuangan pada Sektor Perbankan - Yandira, Meri; Maulana, Alam Nasyah; Ilyas, M.Hakim; Alfarisyi, Salman (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
The utilization of Microsoft Excel in financial reporting within the banking sector has become a common practice due to its flexibility and capability in efficiently managing numerical data. This study aims to identify the extent to which optimizing Microsoft Excel can enhance efficiency and accuracy in the preparation of financial reports in the banking sector. The research method employed is a case study involving several banks that have implemented Microsoft Excel in their financial reporting processes. The findings indicate that leveraging advanced features such as logical functions, PivotTables, and charts in Microsoft Excel can significantly improve time efficiency and reduce errors in financial report preparation. However, challenges remain, including the risk of data input errors and limitations in handling large-scale data processing. The study concludes that optimizing the use of Microsoft Excel can provide substantial benefits in financial reporting within the banking sector, provided it is accompanied by adequate training and stringent oversight.